If you lived here : houses of the world - Laroche, Giles (Houghton Mifflin Books for Children, 2011)
If you lived in the mountains of southern Spain, your bedroom might be carved out of a mountain. If you lived in a village in South Africa, the outside of your house might tell the story of your family. And if you lived in a floating green house in the Netherlands, you could rotate your house to watch both the sunrise and sunset. With intricate bas-relief collages, Giles Laroche uncovers the reason why each home was constructed the way in which it was, then lets us imagine what it would be like to live in homes so different from our own. Showing the tremendous variety of dwellings worldwide<U+2014>log cabins, houses on stilts, cave dwellings, boathouses, and yurts<U+2014>this book addresses why each house is build the way that it is. Reasons<U+2014>such as blending into the landscape, confusing invaders, being able to travel with one's home, using whatever materials are at hand<U+2014>are as varied as the homes themselves.